Meta-heuristic procedure for a step fixed charge transportation problems - Mahmoodirad, Ali; Lagzaie, Leila; Niroomand, Sadegh (American-Eurasian Network for Scientific Information P-112, St.#10,Haseeb Shaheed Colony Hilal Road, Faisalabad, Punjab, 2015)
Background: Step fixed-charge transportation problem is one of the most important problems in transportation research area. That is an extended version of the fixed charge transportation problem. Objective: In the step fixed-charge transportation problem due to the step function structure of the objective function, we are faced with a „„NP- hard?? problem. To tackle such an NP-hard problem, we present Gravitational Search Algorithm (GSA). Results: We solve the randomly generated problems by GSA and also with Genetic Algorithm (GA) to compare them. The obtained results show the proficiency of GSA comparison with GA. Conclusion: We consider step fixed-charge transportation problem in which a NP-hard problem and for solving it proposed the GSA. The results showed that the GSA proposed is more robust and consistently outperformed GA for all instances and sizes. © 2015 AENSI Publisher All rights reserved.
Keywords: Genetic Algorithm; Gravitational search algorithm; Step Fixed Charge Transportation Problem; Transportation Problem